The Political Economy of Food Price Policy in Nigeria - Olomola, Aderibigbe (Oxford University Press, 2015)
The food crisis of 2008 in Nigeria was influenced by price changes in the world market and the escalation of the price of imported fuel into Nigeria which led to sharp increases in the prices of agricultural inputs and transportation cost. The soaring prices of food staples benefited the producers whereas there was a worsening of malnutrition among the poor. To cushion the effects within the short-term, the government released grains from the reserve, ordered the import of half a million tonnes of rice to be sold at a subsidized rate and suspended the tariff on rice imports. The short-term price reduction could not be sustained, however, due to food supply shortages, weakness of the Nigerian currency, and the poor implementation of projects.